(untitled) (Annals of Medical Research, 2022)
Aim: Macrophage activation syndrome (MAS) develops due to increased expression of systemic pro-inflammatory cytokines in patients with the 2019 novel coronavirus disease (COVID-19). Immune modulators have been used in anti-cytokine therapy, with the hypothesis that they can ensure cytokine inhibition and treat cytokine storm. The present study aimed to evaluate inflammatory and prognostic biomarkers in severe COVID-19 cases treated with tocilizumab (TCZ) alone or with the combination of tocilizumab and convalescent plasma transfusion (CPT). Materials and Methods: In this retrospective study, data archives of patients with severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) and who were treated with TCZ alone or the combination of CPT and TCZ were evaluated in line with the literature. The obtained data were statistically evaluated and the alpha significance value was taken as <0.05. Results: Post-treatment C-reactive protein (CRP) (76.19% in TCZ-administered group; 89.32% in TCZ+CPT-administered group) (P<0.05), troponin I (TNI) (25.64% in TCZ-administered group; 90.39% in TCZ+CPT-administered group) (P<0.05), and ferritin (FER) (63.63% in the TCZ-administered group; 9.09% in the TCZ+CPT-administered) (P<0.05) levels were decreased compared to pre-treatment stage. The mean length of hospital stay was longer in the patients treated with TCZ alone (21.55±8.89 days) than in the patients treated with the combination of TCZ and CPT (27.09±13.66 days) (P<0.05). Conclusion: There was no significant difference between the groups in terms of demographic characteristics. The combination of TCZ and CPT treatment did not decrease the mortality. A significant decrease in CRP and TNI levels was observed in the patients treated with TCZ alone and with the combination of TCZ and CPT. A decrease in FER levels showed the effectiveness of the treatments.